"One-stitch" bioorthogonal prodrug activation based on cross-linked lipoic acid nanocapsules. (June 2021) - Wang, Liang; Jing, Pei; Tan, Juan; Liao, Chunyan; Chen, Yun; Yu, Yunlong; Zhang, Shiyong
Abstract: Bioorthogonal prodrug activation is fascinating but suffers from staggered administration of prodrug and trigger, which would not only reduce the therapeutic effect but bring great inconvenience for clinical application. Herein, we report a new cross-linked lipoic acid nanocapsules (cLANCs) based two-component bioorthogonal nanosystem for "one-stitch" prodrug activation. Due to the reversible stability of cLANCs, the loaded prodrug and trigger cannot release in advance while can react upon arrival in the tumor tissue. Moreover, the cLANCs would be degraded into dihydrolipoic acid in tumor cells to potentiate the anticancer effect of the drug synthesized in situ . The data showed that the new bioorthogonal system held a killing effect 1.63 times higher than that of parent drug 3 against human colorectal tumor cells (HT29) and a tumor inhibitory rate 34.2% higher than that of 3 against HT29 tumor xenograft model with negligible side effects. The biodistribution study showed that the "one-stitch" prodrug activation exhibited a selective accumulation of 3 in the tumor tissue compared with free 3 group (34.2 μg vs 3.56 μg of 3 /g of tissue). This two-component bioorthogonal nanosystem based on cross-linked lipoic acid nanocapsules constitutes the first example of "one-stitch" bioorthogonal prodrug activation.